Reentrant spin glass behavior in polycrystalline La0.7Sr0.3Mn1-X FeX O 3 - Xavier Jr.,M.M. (2004)
The magnetic and transport properties of the compound La0.7Sr0.3Mn1-xFe xO 3 (0.1 < x <0.4) have been studied by means of electrical resistivity, AC magnetic susceptibility, and DC magnetization. At low concentrations (x <0.1), the system displays essentially para-to-ferromagnetic transitions as the temperature is decreased, although a decrease in the magnetic moment has been observed in previous studies at temperatures a little below T C. This ferromagnetism is explained by double exchange theory in terms of the formation of Mn+3/Mn+4 ions pairs in the system. At concentrations in the range 0.1 < x <0.4 the system is more complex. Increased Fe doping not only weakens the ferromagnetic (FM) order and augments the resistivity of the samples, but also induces the appearance of a reentrant spin glass phase at low temperatures (T < 60 K). Irreversibility of the magnetization measured with zero field cooling and with field cooling has been observed. In addition, the AC susceptibility peak position varies with frequency. All these effects are characteristic of spin glass behavior. The results have been interpreted based in an increase of frustration due to increasing competition between FM Mn+3/Mn+4 interactions and antiferromagnetic interactions between ions at the boundaries of Fe clusters.